Authenticity assessment of cultivated berries via phenolic profiles of seeds. (15th February 2023) - Krstić, Đurđa D.; Ristivojević, Petar M.; Gašić, Uroš M.; Lazović, Mila; Fotirić Akšić, Milica M.; Milivojević, Jasminka; Morlock, Gertrud E.; Milojković-Opsenica, Dušanka M.; Trifković, Jelena Đ.
Highlights: Each berry fruit species revealed unique phenolic profile of seeds. Advanced chemometric analysis combined with HPTLC profiling enabled authentication assessment. Phenolic compounds relevant for the intercultivar discrimination were identified by UHPLC-LTQ OrbiTrap MS. The resulting mathematical models indicated the ability of the proposed methodology to accurately predict the botanical origin of samples. Abstract: Considering the health-benefits of berry fruits consumption and increased market demands for food authenticity as one of the most important quality assurances, phenolic profiling by high-performance thin layer chromatography and ultra-high-performance liquid chromatography hyphenated with mass spectrometry was combined with multivariate analysis for phytochemical characterization and intercultivar discrimination of cultivated berry seeds. The phenolic profiles of 45 berry seeds from nine genuine Serbian cultivated fruit species (strawberry, raspberry, blackberry, black currant, blueberry, gooseberry, cape gooseberry, chokeberry, and goji berry) revealed a good differentiation according to botanical origin. In order to determine biomarkers responsible for the classification, a total of 103 phenolic compounds were identified, including 53 phenolic acids and their derivatives, 26 flavonoids and 24 glycosides. Biomarkers derived from the phenolic profile of berry seeds proved to be a powerful tool in the authentication of botanical origin, and may be useful in detection of frauds in berry-based seed-containing product.